2011
DOI: 10.4049/jimmunol.1002402
|View full text |Cite
|
Sign up to set email alerts
|

The IL1RN Promoter rs4251961 Correlates with IL-1 Receptor Antagonist Concentrations in Human Infection and Is Differentially Regulated by GATA-1

Abstract: IL-1R antagonist (IL-1Ra) is required for adequate host defense in invasive pneumococcal disease (IPD). The minor allele of an IL1RN gene (C/T) promoter polymorphism (rs4251961) has been shown to be associated with decreased IL-1Ra production in healthy adults. We genotyped 299 children with IPD, and examined 19 IL1RN haplotype-tagging single-nucleotide polymorphisms. Human embryonic kidney HEK293(T) cells were transfected with the promoter reporter plasmid pGL3p containing either allelic variant C (pGL3pCC) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 25 publications
1
38
0
1
Order By: Relevance
“…Examining common variants of the IL1RN gene revealed that the rs4251961 minor allele is associated with a lowered serum level of IL-1RN and that the rs579543 single nucleotide polymorphism (SNP) is also independently associated with IL-1RN levels, whereas the IL1RN 1018 haplotype correlates with higher concentrations of IL-1β and IFNγ 22 . These findings have been confirmed in three independent cohorts 26 , and further research has demonstrated that these factors affect the pathophysiology of human infections 27 and the risk of developing insulin resistance 28 and knee osteoarthritis 29 .…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 60%
“…Examining common variants of the IL1RN gene revealed that the rs4251961 minor allele is associated with a lowered serum level of IL-1RN and that the rs579543 single nucleotide polymorphism (SNP) is also independently associated with IL-1RN levels, whereas the IL1RN 1018 haplotype correlates with higher concentrations of IL-1β and IFNγ 22 . These findings have been confirmed in three independent cohorts 26 , and further research has demonstrated that these factors affect the pathophysiology of human infections 27 and the risk of developing insulin resistance 28 and knee osteoarthritis 29 .…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 60%
“…Namely, plasma IL-1Ra concentrations were significantly higher in nonsurvivors compared with survivors, and the major (C) allele of rs4251961 was associated with a significant increase in plasma IL-1Ra. 23 The minor allele has been previously shown to be associated with decreased IL-1Ra production in healthy adults.…”
Section: Infections Chronic Inflammationsmentioning
confidence: 98%
“…Elevated circulating IL-1Ra concentrations are also associated with increased levels of infection in patients with respiratory disease [79,84,85] and with post-stroke infection [86]. This may indicate that increased IL-1 activity and reduced host defence against the infectious agents occur.…”
Section: Infection and Stroke: A Role For Il-1 And Other Proinflammatmentioning
confidence: 99%